FASiAL PARALiZiDE AL TIN AGIRLIK iLE UST GOZ KAPAGINA FONKSiYON KAZANDIRILMASI - AYGIT, A.Cemal; AYHAN, M.Semih; BAYÇIN, H.Nazmi (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In order to gain functional and cosmetic improwment in the lagophtalmos due to facial paralyses, gold weight was inserted into upper eyelid. Sewn cases with paralytic lagophtalmus due to facial paralyses were treated with gold weight implantation between July 1997-August 1998 in our department. Each patient had 24-carat gold weight inserted into a small pocket between the orbicularis muscle and the tarsal plate of the upper eyelid. Results.- Complete eyelid closure and restoration of blink reflex were obtained in all patients at the postoperatiw examination. There was no corneal irritation symptoms. One patient was operated again because of implant migration. Conclusion.- This technique is simple to perform, has a relatiwly low complication rate and produces an acceptable functional and cosmetic result.